MENANAMKAN DISIPLIN PADA ANAK USIA DINI - Harjanty, Rokyal; Mujtahidin, Samsul (LPPM Institut Pendidikan Nusantara Global, 2022)
Discipline in children was to provide an understanding of what is good for them and what is bad. Discipline education needs to be instilled in children that making mistakes certainly has a number of consequences, because the reason for that is the function of punishment in children's education. Discipline is a value behavior that can be done by force and can be done voluntarily. For early childhood, this form of discipline must be implemented voluntarily and through play. Teachers, society and parents are the most influential factors for disciplining children.